MAHASANTRI METACOGNITIVE STRATEGY TADRIS MATHEMATICS STUDY PROGRAM IN SOLVING QUESTIONS BASED ON HIGHER ORDER THINKING SKILLS (HOTS) - Sangsongko, M Agus; Maryono, Maryono; Mu’awanah, Elfi (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Higher order thinking abilities or Higher Order Thinking Skills (HOTS) is a crucial aspect in mathematics education, especially in producing graduates who are able to think critically, creatively and reflectively. However, many students still experience difficulties in solving HOTS-based questions due to a lack of systematic thinking strategies. Metacognitive strategies is an approach that can help students plan, monitor and evaluate their thinking processes effectively. Therefore, this research aims to explore the application of metacognitive strategies in solving HOTS questions among students of the Tadris Mathematics Study Program and identify the factors that influence their success. This research uses system literature review (SLR) method by reviewing various academic sources related to metacognitive strategies in learning mathematics. The research results show that metacognitive strategies play an important role in increasing the effectiveness of HOTS learning, where students who have good metacognitive awareness are better able to develop flexible and systematic problem solving strategies. Factors that influence the success of this strategy include students' cognitive readiness, the role of lecturers in learning, a conducive learning environment, and curriculum policies that support the development of higher order thinking skills. The conclusion of this research confirms that metacognitive strategies must be integrated optimally in mathematics learning to improve students' HOTS skills. The main recommendation from this research is the need for training for lecturers and students regarding metacognitive strategies as well as improving the curriculum so that it is more oriented towards developing critical and reflective thinking skills.